Isosteric heat of sorption in powders produced from agro-industrial byproducts: a systematic review and meta-analysis (Scientia Agropecuaria, 2026)
This systematic review and meta-analysis aimed to analyze data published since 2007 on the isosteric heat of sorption ( ) in powdered foods derived from agro-industrial by-products, in order to support the optimization of dehydration processes and their sustainable use in the food industry. Twenty-five studies were included following a structured search strategy. Results showed that powdered by-products predominantly exhibit Brunauer type II (sigmoidal) and type III isotherms, strongly influenced by their composition. Type II curves were associated with protein-, starch-, and biopolymer-rich powders, while type III behavior characterized sugar- and fiber-rich matrices. The Guggenheim–Anderson–de Boer (GAB) model consistently provided the best fit (R² > 0.90), with monolayer moisture content ( ) ranging from 0.006 to 0.6 g water/g dry matter and generally decreasing with temperature. Cluster analysis grouped powders according to  values, composition, and temperature, highlighting the role of matrix structure in water retention behavior. The isosteric heat of sorption ( ) exhibited both endothermic and exothermic behavior (–88.4 to 58.0 kJ/mol), with higher energy requirements during desorption. Principal Component Analysis (PCA) revealed that  is mainly associated with fiber-rich matrices, whereas the GAB parameter C is linked to carbohydrate and lipid fractions. In contrast,  showed weak association with the principal components, indicating that sorption energetics are not directly aligned with structural variability but rather reflect localized molecular interactions. Overall, sorption behavior of powdered by-products is governed by the combined effect of composition, structural water retention, and energetic interactions, which are critical for improving drying and storage conditions.